Impact of Gross Domestic Product Per Capita and Population on United Arab Emirates Trade Volume - Hassan, Ethar; Agbolosoo, John Atsu; Nurmalina, Rita; Rifin, Amzul (Universitas Airlangga, 2025)
The United Arab Emirates (UAE) has become a significant global trade hub. Understanding the factors influencing trade flows is crucial for developing effective strategies to promote trade activities and sustain economic growth. This study examines the impact of Gross Domestic Product (GDP) per capita and population size on trade flows in UAE with major trading partners, including China, Germany, Iraq, India, Japan, and Saudi Arabia, by utilizing a fixed-effects gravity model and panel data from 2000 to 2020. A positive relationship was found between the GDP of UAE and trading partners and bilateral trade, and a negative relationship was found between GDP per capita, the population of UAE, and bilateral trade flows. The distance between the capital city of UAE and its trading partners also has a negative effect on bilateral trade flows. This study suggests that trading partners should improve their GDP per capita. The negative impact of the increasing population size of the UAE on bilateral trade flows indicates that the UAE should improve labor quality and skills that may enhance trade growth and economic development and that trade policies between UAE and its trading partners need to address trade barriers and initiate efforts for their eradication to improve bilateral trade. The policy implication is that trade opportunities should be expanded by exploring trade agreements and fostering diversification of export goods to mitigate domestic competition and open new markets.